Investor Protection and Corporate Governance : Firm-Level Evidence Across Latin America - Chong, Alberto; López-de-Silanes, Florencio (Palo Alto, CA: Stanford University Press, 2012)
This book holds that the crucial failure of corporate governance is the expropriation of outside investors, be they shareholders or creditors, by those who are in control of firms. The problem of expropriation, also known as tunneling, often takes on enormous proportions. Billions of dollars of wealth are siphoned away from outside investors to controlling shareholders and their private company allies. The expropriation prevents investors from devoting funds in the corporate sector, thus leading to low valuations of corporate assets, stunted capital markets, and slowed economic growth. Low valuations and underdeveloped financial markets are only two of the symptoms of investor expropriation. Other symptoms include concentrated corporate ownership, large spreads between cash flow ownership and the voting rights of dominant shareholders, pyramids, and low dividend payments. When financial markets exhibit these symptoms, the likely underlying problem is investor expropriation. The essays collected in this volume put together a compelling picture showing that many of the symptoms of investor expropriation and poor corporate governance are present in Latin America. The evidence is loud and clear in every chapter of this book. But there are also benefits to collecting this detailed proof. The evidence suggests recipes for improvement as well. The message of this book is as unambiguous as is its analysis: a critical goal in the agenda of financial reform in Latin America must be improvement in corporate governance through legal reform.